Effect of COVID-19 pandemic on the well-being and training of medical interns: an experience from a university of Eastern India - Madhusikta, Smriti; Mohapatra, Ipsa; Panoria, Subodh (Indian Journal of Community Health, 2022)
Background: COVID-19 pandemic changed routines, with social distancing, quarantines, online classes, negatively affecting the mental health of the medical fraternity.Objectives: To assess the impact of COVID-19 pandemic on the mental well-being and training and identify stressors experienced by medical-interns.Methods: A cross-sectional study among 150 interns, from 1st June- 30th September 2021, using Google form with 3sections-demographics, stressors experienced during the pandemic and WHO well-being index; data analyzed using EPI INFO software en-US version7.2.3.1.Results: of the 150 interns, 138 responded. Mean-age was 25.19 ± 1.62SD years; 60.8% were males, 56.5% were hostellers,30% suffered from COVID-19. 78.9% stated “lack of supervision during postings”, 73.9%“postponement of NEET PG” and 60.8%“lack of learning opportunities” as reasons of stress. 65.2% had a good “WHO well-being index”. Their COVID-19 infectivity status had a statistically significant (p=0.004) association with WHO well being index. “Lack of learning opportunities”(p=0.02), “fear of contracting COVID-19”(p=0.03) & “limited time for PG preparation(p=0.01) were associated with their well-being.Conclusion: COVID-19 was associated with stress and poor mental health among the interns. Fear of disease, lack of regular duties and postponement of PG exams were factors leading to stress. Lack of learning opportunities, fear of contracting the virus were associated with poorer mental well-being.